Diseño de revestimiento y cementación de pozos en el oriente ecuatoriano - Morán Palacios, William (2009)
The proper selection of the casing is an important factor in the planning, organization and operations of an oil well, and cementation also plays an important role in the life of the well, since the work of a good completion depends directly in a good cementing. The present paper focuses on demonstrating an alternative to the current design of the well ESPOL X6-D using the method of Design by Trial and Error, along with their cementing program. It highlights the history of the well, describing the location where the field was drilled, lithological features and basic approaches about the drilling program implemented. It also describes basic concepts of casing and cementing of wells along with the methods used, and then proceeds with the redesign of the casing and the volume of slurry used to cement them. Finally a quantitative comparison of the proposed design with the current design is made to define whether or not it was possible to achieve the optimization of it.